ANALISIS PENGARUH KINERJA KEUANGAN TERHADAP HARGA SAHAM PT BNI PERSERO TBK - Rahmat Arapi; Daniel Nemba Dambe (JURNAL ULET (Utility, Earning and Tax), 2019)
This study aims to determine how much the influence the market performance directly on BBNI stock prices and the influence through purchasing decisions. Market performance in this case is represented by market value ratios, including Earning Per Share, Price Earning Ratio and Price Book Value. The study used a descriptive and associative approach. Descriptive approach to know the condition of BBNI's financial performance using market value ratios. While the associative approach to determine the effect of financial performance on stock prices through purchasing decisions using path analysis. Data collection is done by documentation and literature study techniques. The results showed that EPS directly or indirectly had a significant effect on BBNI stock prices. PER directly or indirectly has an effect but not significantly on BBNI stock prices. PBV directly or indirectly has an effect but not significantly on BBNI stock prices.